Research the Impact of Trade Facilitation on Trade between Vietnam and ASEAN: Empirical Analysis Based on Commercial Gravity Model - Ming, Cui Ri; Day, Dao Van (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2019)
This research aims to calculate and measure the level of trade facilitation of ASEAN countries. The research selected five indicators of trade facilitation, including infrastructure, customs environment, e-commerce, policies environment and financial environment, to measure the degree of trade facilitation of ASEAN countries and used the Gravity model to empirically analyze the effect of trade facilitation of the ASEAN countries to trade between Vietnam - ASEAN. The study shows that trade facilitation profoundly affects Vietnam’s export and import flow. Based on the analysis results, the paper suggests some recommendations to boost Vietnam’s trade facilitation.